Teachers' Efforts to Form Student Learning Independence at UPT SPF SD Inpres Mangga Tiga Makassar - Sugianto, Sugianto; Yunus, Muh; Fahreza W, Muhammad (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine, 1) Student Learning Independence and, 2) determine the efforts made by teachers in forming Student Learning Independence at UPT SPF SD Inpres Mangga Tiga Makassar. The method used in this research is a qualitative approach. The methods are 1) Observation, 2) Interview and 3) Documentation. The results of the research show that students' learning independence at UPT SPF SD Inpres Mangga Tiga Makassar, students' learning independence from hearing the teacher's explanation is generally said to be good, students are enthusiastic about listening to the teacher's explanation, when the teacher gives an explanation there are some students who talk to their friends or do other activities, but there are not many of them. The teacher's efforts in forming independent learning for UPT SPF SD Inpres Mangga Tiga Makassar students, namely: 1) Making plans, the teacher has outlined all the plans in the syllabus and lesson plan. The preparation of the Learning Implementation Plan (RPP) made by the teacher is developed in the syllabus. 2) Implementation, the teacher's role in forming student learning independence can be seen from the media used, namely video and image displays using Power Point, as well as using discussion, question and answer, problem solving, socio-drama and assignment methods. 3) Evaluation in the learning process to obtain information on the achievement of learning objectives which is carried out continuously.